Cucumber (Cucumis sativus L.) Seedling Rhizosphere Trichoderma and Fusarium spp. Communities Altered by Vanillic Acid - Chen, Shaocan; Yu, Hongjie; Zhou, Xingang; Wu, Fengzhi (Frontiers in Microbiology, 2018)
Root exudates mediate soil microbiome composition and diversity, which might further influence plant development and health. Vanillic acid from root exudates is usually referred as autotoxin of cucumber, however, how vanillic acid affect soil microbial community diversities and abundances remains unclear. In this study, vanillic acid (VA; 0.02, 0.05, 0.1 and 0.2 μmol g-1 soil) was applied to soil every other day for a total of five applications. We used Illumina MiSeq sequencing, quantitative PCR (qPCR) and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) to test the effects of VA on the total fungi community composition as well as the Trichoderma and Fusarium spp. community abundances and structures in the cucumber rhizosphere. Illumina MiSeq sequencing showed that VA (0.05 μmol g-1 soil) increased the relative abundance of the fungal phylum Basidiomycota while decreasing the relative abundance of Ascomycota (P < 0.05), and not altered the diversity of the soil fungal community. VA (0.05 μmol g-1 soil) also increased the relative abundances of the fungal genera with plant pathogens, such as Conocybe and Spizellomyces spp.(P < 0.05). A qPCR analysis showed that VA (0.05 to 0.2 μmol g-1 soil) exerted promoting effects on Trichoderma spp. community abundance and stimulated Fusarium spp. abundance at low concentrations (0.02 to 0.05 μmol g-1 soil) but inhibited it at high concentrations (0.1 to 0.2 μmol g-1 soil). The PCR-DGGE analysis showed that all concentrations of VA altered the community structures of Trichoderma spp. and that the application of VA (0.02 and 0.05 μmol g-1 soil) changed the band number and the Shannon-Wiener index of the Fusarium spp. community. This study demonstrated that VA changed the total fungal community in the cucumber seedling rhizosphere and that the Trichoderma and Fusarium spp. communities showed different responses to VA.